A Rare Cause of Dysphagia and Cough: Bronchoesophageal Fistula from Silicosis. Issue 1 (2018) - Lieber, Sarah R.; Ettenger, Norman; Atlas, Steven A.
ABSTRACT : N/A: Dysphagia and cough in an older male smoker raise concern for malignancy. However, a history of environmental exposures led to a much more interesting diagnosis in this case of pneumoconiosis due to silicosis. Silicosis is an uncommon pulmonary disease with rare associated gastrointestinal symptoms. We report a bronchoesophageal fistula resulting from silicosis causing dysphagia and cough. This is the first report of using endoscopic stenting to manage an esophageal fistula from silicosis. This case highlights how common symptoms of cough and dysphagia can masquerade as a pulmonary or oropharyngeal problem, when they are actually gastrointestinal manifestations of a rare disease.